Numerical and experimental research of cold storage for a novel expanded perlite-based shape-stabilized phase change material wallboard used in building. (1st January 2018) - Yao, Chengqiang; Kong, Xiangfei; Li, Yantong; Du, Yaxing; Qi, Chengying
Highlights: A PCM wallboard was prepared by horizontal vacuum absorption rotate roller. PCM wallboard was experimentally investigated in cube for thermal performance. A one-dimensional heat transfer model of PCM wallboard was developed and validated. The optimal configuration parameters were obtained by numerical modeling. Abstract: Phase change material (PCM) used in building can enhance the thermal inertia of building and improve the indoor thermal comfort. A novel shape-stabilized phase change material wallboard (PCMW), in which paraffin was as the PCM and expanded perlite (EP) was the supporting material, has been prepared through a horizontal vacuum absorption rotate roller (HVARR) in this study. Its melting point and freezing point were measured to be 27.60 °C and 23.56 °C, respectively, and the melting and freezing latent heats reached to be 67.13 J/g and 67.06 J/g, respectively. PCMW was experimentally and numerically studied to analyze the thermal performance. The experimental result in 5 days, which was a demonstration in a container subject to weather conditions typical for the north China, showed that PCMW used in the building can maximally reduce the indoor temperature of 2.53 K. For the numerical study, based on the equivalent heat capacity method, a one-dimensional heat transfer model of PCMW was developed and combined with TRNSYS. This model was validated by the experimental data, and the numerical data agreed well with the experiment data. Under the summer condition, the numerical study of PCMW used in a typical office building during two months showed PCMW can averagely reduce the temperature of 9.22 K in the building operation time (7:00–18:00). Besides, according to the numerical model, an optimal configuration of PCMW in the cold zone of China has been obtained. The studied method provides a comprehensive guide to the PCMW design and application.